Plant community trajectories following livestock exclusion for conservation vary and hinge on initial invasion and soil‐biocrust conditions in shrub steppe - Matthew J. Germino; Chad R. Kluender; Christopher R. Anthony (Conservation Science and Practice, 2022)
Abstract Adjustments or complete withdrawal of livestock grazing are among the most common conservation actions in semiarid uplands, but outcomes can vary considerably with ecological context. Invasion by exotic annual grasses and the excessive wildfire they promote are increasing threats to semiarid shrub‐steppe, and plant‐community response to livestock exclusion in these areas may be complicated by the rapid colonization ability of invaders. We evaluated vegetation‐community changes over 14‐year interval (2007–2021) in a shrub‐steppe landscape where a >100‐year history of livestock grazing had been terminated in 1996. Field surveys revealed that bare‐soil exposure decreased >20% over the 14 years owing to biomass accumulation, but this was primarily due to large increases in exotic annual “cheatgrass” (Bromus tectorum, +1.8‐fold) and the litter it produces (+1.5‐fold). Soil biocrusts increased 11.9% and perennial bunchgrasses increased 3% over the 14 years. These community changes varied at the patch scale and entailed inverse relationships of (1) both cheatgrass and biocrusts to plant‐community basal cover, (2) cheatgrass to both biocrusts and perennial grasses, and (3) biocrusts to cheatgrass and litter. The spatiotemporal variability in vegetation constituted changes in plant‐community states, according to cluster analysis. The modeled probability of a community transitioning to a cheatgrass state was (1) strongly and positively related to the initial (2007) cover of cheatgrass in hotspots where initial cheatgrass cover was >20%, and (2) negatively related to biocrust cover where initial biocrust cover was >4% of ground area. The decision space for this landscape can be framed as a shifting from acceptance towards resisting further degradation by removing livestock and their trampling of soil surfaces and utilization of perennial herbs. However, cheatgrass appears to be the most impactful agent of change and continued invasion appears imminent. Active restoration may help resist further degradation and direct change towards tolerable conditions.